Loss of transcriptional control over endogenous retroelements during reprogramming to pluripotency - Friedli, Marc; Turelli, Priscilla; Kapopoulou, Adamandia; Rauwel, Benjamin; Castro-Díaz, Nathaly; Rowe, Helen M.; Ecco, Gabriela; Unzu, Carmen; Planet, Evarist; Lombardo, Angelo; Mangeat, Bastien; Wildhaber, Barbara E.; et al. (Genome Research, 2014)
Endogenous retroelements (EREs) account for about half of the mouse or human genome, and their potential as insertional mutagens and transcriptional perturbators is suppressed by early embryonic epigenetic silencing. Here, we asked how ERE control is maintained during the generation of induced pluripotent stem cells (iPSCs), as this procedure involves profound epigenetic remodeling. We found that all EREs tested were markedly up-regulated during the reprogramming of either mouse embryonic fibroblasts, human CD34+ cells, or human primary hepatocytes. At the iPSC stage, EREs of some classes were repressed, whereas others remained highly expressed, yielding a pattern somewhat reminiscent of that recorded in embryonic stem cells. However, variability persisted between individual iPSC clones in the control of specific ERE integrants. Both during reprogramming and in iPS cells, the up-regulation of specific EREs significantly impacted on the transcription of nearby cellular genes. While transcription triggered by specific ERE integrants at highly precise developmental stages may be an essential step toward obtaining pluripotent cells, the broad and unspecific unleashing of the repetitive genome observed here may contribute to the inefficiency of the reprogramming process and to the phenotypic heterogeneity of iPSCs.
10.1101/gr.172809.114